Evaluation of the relationship between lifestyle balance, emotional regulation, and relapse with individuals with drug and/or alcohol problems : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Science in Psychology at Massey University, Albany, New Zealand - Dicks, Casey William (Massey University, 2013)
Drug and alcohol abuse costs the country over $5.3 billion per year (Slack, Nana, Webster, Stokes, & Wu, 2009). Treatment can reduce both the health and social cost of drug and alcohol abuse (Rout, 2008) but relapse remains a major problem (Stewart, 2000). Studies have shown lifestyle balance and emotion regulation are important factors in relapse prevention (Thakker & Ward, 2012; Matto, Strolin & Mogro-Wilson, 2008). This study explored the relationship between lifestyle balance, emotion regulation and relapse with 25 participants, aged between 18 and 55, actively seeking treatment through CADS North Action group. Participants reported their subjective lifestyle balance, emotion regulation, and whether they had relapsed, at three time periods (pre-, mid-, and post-treatment). Relapse rates were 56% at pre-, 42% at mid-, and 25% at post-treatment. Results indicate a positive relationship between lifestyle balance and relapse, which suggests that as lifestyle balance improves relapse decreases. Results also indicate that, as emotion regulation improves relapse decreases. A newly developed lifestyle balance questionnaire (LBQ) showed good psychometric properties, which were comparable with existing measures. This study addresses a gap in the literature on the relationship between lifestyle balance, emotion regulation and relapse, in a drug and alcohol population, and seems to be the first of its kind in New Zealand. Limitations of the research and future directions are discussed.
Keywords: Substance abuse relapse; Work-life balance; Self-control; Emotions; Drug addicts; Alcoholics; Rehabilitation